Hubungan Status Gizi Dengan Gerak Motorik Anak Usia 12-18 Bulan Di Posyandu Nusa Indah, Kampung Cakung, Jati Sari, Jatiasih, Kota Bekasi : The Relationship between Nutritional Status and Motor Movement of Children Aged 12-18 Months at Integrated Healthcare Center Nusa Indah, Cakung Village, Jati Sari, Jatiasih, Bekasi City - Kasilah, Dina (Dohara POAJ, 2023)
Introduction: Based on a preliminary study at Integrated Healthcare Center Nusa Indah there is still a high rate of 60% of children under five with poor nutritional status and 40% of good nutrition, so it can be formulated in this study that still high rate of poor nutritional status can affect the motor movements of children aged 12-18 months at Integrated Healthcare Center Nusa Indah in 2022. Therefore, researchers are interested in researching on how nutritional status is related to the motor movements of children aged 12-18 months at Integrated Healthcare Center Nusa Indah, Cakung Village, Jatisari, Jatiasih, Bekasi City in 2022. Methods: This research was conducted as a quantitative study with an analytic descriptive design that looks at the relationship between the independent variable (children's nutritional status) and the dependent variable (children's motor skills). form of research design by observing or measuring simultaneously (at one time) between the independent variable and the dependent variable (Notoatmodjo 2018) Sampling Technique was used with accidental sampling (mothers who come to Integrated Healthcare Center Nusa Indah). Results: There is a significant relationship between the dependent variable, namely gross motor movements of children aged 12-18 months, and the independent variable nutritional status of children aged 12-18 months at Integrated Healthcare Center Nusa Indah, Cakung Village, Jati Sari, Jatiasih, Bekasi City in 2022, where the p-value is 0,000 < 0,050. Discussion: Broadly speaking, there is an effect of red ginger powder (Zingiber officinale var Rubrum) on reducing the intensity of dysmenorrhea pain in female students at SMAN 1 Muncang, Lebak Regency, Banten before and after consuming red ginger powder (Zingiber officinale var. Rubrum) as evidenced by the results of statistical tests using One-Sample Statistics with a significance value of p 0.000.